MOF composite microsphere material and preparation method thereof
By mixing MOF powder with hydrophilic polymer organic polymer and binder, polymerization and granulation treatment, MOF composite microsphere material is prepared, which solves the operability and mechanical strength problems of MOF powder in practical applications, and achieves the efficient water absorption and good mechanical properties of the material.
Patent Information
- Application Number
- CN202411768537.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
Smart Images

Figure CN119588322A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and more specifically, to a MOF composite microsphere material and a preparation method thereof. Background Art
[0002] At present, the research direction of atmospheric water harvesting is mainly focused on the development of new adsorption materials, such as metal organic frameworks, zeolites, silica gel and other porous materials, which have high adsorption capacity, good stability and regeneration. In recent years, metal organic framework materials (MOF) have shown great potential in the field of atmospheric water harvesting due to their high specific surface area and adjustable pore structure. Compared with the characteristics of traditional water-absorbing materials such as high water absorption capacity but large dehydration resistance, MOF can efficiently adsorb water molecules in a relatively low humidity environment and release them quickly under suitable conditions, thereby achieving the purpose of collecting water from the air. On the other hand, MOF powder materials are difficult to use directly, and have the characteristics of slow mass transfer, easy loss, and difficult recycling. In addition, pure MOF materials will be limited by low water absorption capacity and energy-intensive regeneration processes. Therefore, combining MOF with molding materials to form a monolithic material of MOF can further adjust the water absorption properties of MOF materials while processing MOF materials into a morphology that is convenient for practical application, providing a new way for the application scenarios of MOF materials. This type of material inherits the advantages of MOF's porosity, high specific surface area and adjustable chemical properties, while improving the mechanical stability, handling ability and application flexibility of MOF in practical applications through the optimization of macroscopic morphology. Common methods for synthesizing MOF monolithic materials include substrate growth, mechanical compression, gelation and bonding molding. Compression or gelation may cause a certain degree of porosity loss and a decrease in specific surface area of the material. In the bonding method, when the selected binder itself can contribute to a part of the performance effect, the resulting overall material will achieve a synergistic improvement in performance.
[0003] CN117841320A discloses a method for preparing injection molded products using metal organic framework materials. The method can effectively mix MOF materials with thermoplastic resins, and prepare composite materials with excellent mechanical properties, gas adsorption properties and catalytic properties through injection molding process. The invention includes the following steps: mixing thermoplastic resin materials and MOF materials in a ratio of 1:1 to 9:1, granulating after drying, and then sending them into an injection molding machine for injection molding to obtain finished products; the thermoplastic resin material is polypropylene or polyethylene or polystyrene or polycarbonate or polyethylene terephthalate or nylon. The prepared finished product has high mechanical properties, such as tensile strength of 45MPa, bending strength of 65MPa, and impact strength of 12kJ / m 2At the same time, the product also has good gas adsorption performance, such as the adsorption capacity of CO2 is 1.2mmol / g, the adsorption capacity of CH4 is 0.8mmo1 / g, and the selectivity of CO2 / CH4 is 1.8. In addition, the product also has good thermal stability and water stability, and can be used for a long time in an environment of 100℃ and 90% humidity without losing its structure and function.
[0004] CN112705168A discloses a method for forming an ultra-microporous MOF adsorbent material, comprising the following steps: adding polyvinyl alcohol (PVA) to water, heating and stirring to form a colloidal aqueous solution of PVA; stirring the ultra-microporous MOF adsorbent powder and an appropriate amount of methyl cellulose (MC) evenly; adding the prepared PVA aqueous solution, mixing and stirring, forming and granulating, and drying to obtain spherical particles. The particle size of the spherical particles is 3 to 5 mm, the mechanical strength is >20N / particle, the adsorption performance for C2H6 is more than 89% of the adsorption performance of the ultra-microporous MOF adsorbent powder, and the thermal stability is maintained above 500°C.
[0005] CN113272053A discloses a MOF extrusion material and a method for manufacturing the same, comprising the following steps: mixing a pre-crystallized MOF powder material with a solvent selected from alcohol and alcohol / water, and extruding the ground MOF paste to obtain a MOF extrusion material. The BET of the MOF extrusion material is equivalent to 50% of the pre-crystallized MOF powder material, and the proportion of the pre-crystallized MOF powder material converted into different phases in the extrusion material accounts for 20%.
[0006] The above existing solutions mostly use the method of physically mixing MOF powder materials with high molecular polymers to optimize the poor mass transfer capacity of MOF powder in practical applications and improve the mechanical properties and gas adsorption performance of the material. However, the preparation of MOF powder requires a drying process, which causes additional energy consumption, and few solutions have studied the water vapor adsorption characteristics and water collection performance of MOF molded composite materials. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide a MOF composite microsphere material and a preparation method thereof, so as to solve the problems of poor operability, limited mass transfer and poor mechanical strength of powdered MOF; the preparation method provided by the present invention obtains a formed composite material by granulation, which has the advantages of both MOF and polymer, and prepares the material into a granular material with controllable size, certain mechanical strength, and excellent water absorption performance in various humidity ranges, which is suitable for actual application scenarios.
[0008] The present invention provides a method for preparing a MOF composite microsphere material, comprising the following steps:
[0009] a) adding 3,5-pyrazoledicarboxylic acid into water to dissolve it, then adding hydroxyaluminum and an inorganic base to react, washing and drying to obtain MOF powder;
[0010] b) mixing the MOF powder obtained in step a) with a hydrophilic high molecular organic polymer, a binder and water, adding N,N-methylenebisacrylamide, introducing nitrogen into the system, and finally adding an initiator to carry out a polymerization reaction to obtain a reaction mixture slurry;
[0011] c) dripping the reaction mixture slurry obtained in step b) into a curing agent for granulation, washing and freeze-drying to obtain a MOF composite microsphere material.
[0012] Preferably, the dissolving process in step a) is specifically as follows: adding water to a beaker, then adding 3,5-pyrazoledicarboxylic acid, placing the beaker in a water bath, and completely dissolving at 60° C. to 80° C. until the solution is clear and transparent;
[0013] The inorganic base is selected from NaOH and / or KOH;
[0014] The reaction temperature is 85°C to 95°C and the reaction time is 0.5h to 1.5h;
[0015] The washing method is specifically to use water and methanol to wash 1 to 3 times respectively;
[0016] The drying temperature is 85° C. to 95° C., and the drying time is 10 h to 30 h.
[0017] Preferably, the hydrophilic high molecular organic polymer in step b) is selected from polyisopropylacrylamide and / or polyacrylic acid.
[0018] Preferably, the binder in step b) is selected from one or more of sodium alginate, sodium carboxymethyl cellulose, polyvinyl alcohol and polyvinyl pyrrolidone.
[0019] Preferably, the mass ratio of the hydrophilic high molecular organic polymer to the binder in step b) is 1:(0.5-2).
[0020] Preferably, the initiator in step b) is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobisisobutylamidine hydrochloride, hydrogen peroxide, ammonium persulfate, potassium persulfate, benzoyl peroxide, tert-butyl benzoyl peroxide, and methyl ethyl ketone peroxide.
[0021] Preferably, the polymerization reaction in step b) is carried out at a temperature of 0°C to 80°C and for a time of 0.5h to 1h.
[0022] Preferably, the curing agent in step c) is selected from one or more of calcium chloride solution, aluminum sulfate solution and copper sulfate solution.
[0023] Preferably, the granulation process in step c) is specifically as follows:
[0024] The reaction mixture slurry is dripped into the curing agent, and the beads are cross-linked in the curing agent for 20 to 40 minutes and then washed with water;
[0025] The freeze-drying process is specifically as follows:
[0026] The washed beads were frozen in liquid nitrogen for 5 to 15 minutes, and then the material was placed in a freeze dryer for freeze drying to obtain a MOF composite microsphere material.
[0027] The present invention also provides a MOF composite microsphere material, which is prepared by the preparation method described in the above technical solution.
[0028] The invention provides a method for preparing a MOF composite microsphere material, comprising the following steps: a) adding 3,5-pyrazoledicarboxylic acid into water to dissolve it, then adding hydroxyaluminum and an inorganic base to react, washing and drying to obtain MOF powder; b) mixing the MOF powder obtained in step a) with a hydrophilic macromolecular organic polymer, a binder and water, then adding N,N-methylenebisacrylamide, introducing nitrogen into the system, and finally adding an initiator to carry out polymerization reaction to obtain a reaction mixture slurry; c) dripping the reaction mixture slurry obtained in step b) into a curing agent to granulate, washing and freeze-drying to obtain the MOF composite microsphere material. Compared with the prior art, the preparation method provided by the present invention selects specific raw materials and specific process steps to achieve better overall interaction: directly using the dispersion system in the MOF preparation process, adding hydrophilic high molecular organic polymer and binder, and then dripping the slurry into the curing agent with a peristaltic pump for granulation to obtain uniform MOF composite microspheres; by adding molding materials and functional materials, the original MOF powder has a plastic shape, certain mechanical strength, excellent water absorption performance, desorption capacity and circulation performance. The experimental results show that the MOF composite microsphere material prepared by the preparation method provided by the present invention has the advantages of both MOF and polymer, and is controllable in size, good in mechanical strength, and excellent in water absorption performance in various humidity ranges, and can be applied to various practical application scenarios.
[0029] At the same time, the preparation method provided by the present invention has simple process, mild conditions, easy control, low energy consumption and thus energy saving, strong water collection performance, environmental friendliness, and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the preparation process of the present invention;
[0031] Figure 2Optical photos of PNIPAM / MOF-4 microspheres before (a) and after (b) water absorption;
[0032] Figure 3 The water vapor adsorption curve comparison of the formed PNIPAM / MOF composite microspheres and the original MOF-303. Figure 3 The annotated PNIPAM / MOF-1, 2, 3, 4, 5, 6, and 7 are indicated as the example section. The addition amounts of NIPAM:SA (g) are 0.8:0.2, 0.7:0.3, 0.6:0.4, 0.5:0.5, 0.4:0.6, 0.3:0.7, and 0.2:0.8, respectively;
[0033] Figure 4 The effect of PAA with different neutralization degrees on the water vapor adsorption capacity of PAA / MOF microspheres;
[0034] Figure 5 The effect of different binders on the water vapor adsorption capacity of PAA / MOF microspheres;
[0035] Figure 6 The effect of different curing agents on the water vapor adsorption capacity of PAA / MOF microspheres;
[0036] Figure 7 Optical photos of PAA / MOF-1 microspheres before (a) and after (b) water absorption;
[0037] Figure 8 is the water vapor adsorption of PAA / MOF microspheres at RH = 10% (a), RH = 20% (b), RH = 50% (c) and RH = 80% (d), where Figure 8 The annotated PAA / MOF-1 and 2 are examples in which the addition amounts of AM are 0 and 0.2 g, respectively. The addition amounts of other reagents are detailed in Table 2. DETAILED DESCRIPTION
[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] The present invention provides a method for preparing a MOF composite microsphere material, comprising the following steps:
[0040] a) adding 3,5-pyrazoledicarboxylic acid into water to dissolve it, then adding hydroxyaluminum and an inorganic base to react, washing and drying to obtain MOF powder;
[0041] b) mixing the MOF powder obtained in step a) with a hydrophilic high molecular organic polymer, a binder and water, adding N,N-methylenebisacrylamide, introducing nitrogen into the system, and finally adding an initiator to carry out a polymerization reaction to obtain a reaction mixture slurry;
[0042] c) dripping the reaction mixture slurry obtained in step b) into a curing agent for granulation, washing and freeze-drying to obtain a MOF composite microsphere material.
[0043] The present invention first adds 3,5-pyrazole dicarboxylic acid (H2PZDC) into water to dissolve, then adds hydroxyaluminum (HCA) and an inorganic base to react, and then washes and dries to obtain MOF powder. The present invention has no special restrictions on the sources of the 3,5-pyrazole dicarboxylic acid (H2PZDC) and hydroxyaluminum (HCA), and commercially available products known to those skilled in the art can be used.
[0044] In the present invention, the water is preferably deionized water well known to those skilled in the art.
[0045] In the present invention, the dissolution process adopts a heating and stirring method, and the stirring speed is preferably 50rpm~500rpm. The stirring involved in the following preparation process is applicable to this speed range, and the present invention will not repeat it; the dissolution process is preferably specifically as follows: add water to a beaker, then add 3,5-pyrazoledicarboxylic acid, place the beaker in a water bath, and completely dissolve at 60°C~80°C until the solution is clear and transparent.
[0046] In the present invention, the inorganic base is preferably selected from NaOH and / or KOH, more preferably NaOH; the present invention has no special limitation on the source of the inorganic base, and commercially available products known to those skilled in the art can be used.
[0047] In the present invention, the reaction temperature is preferably 85° C. to 95° C., and the reaction time is preferably 0.5 h to 1.5 h.
[0048] In the present invention, the washing method is preferably to use water and methanol for washing 1 to 3 times respectively.
[0049] In the present invention, the drying temperature is preferably 85° C. to 95° C., and the drying time is preferably 10 h to 30 h.
[0050] After obtaining the MOF powder, the present invention mixes the obtained MOF powder with a hydrophilic high molecular organic polymer, a binder and water (preferably by heating and stirring), then adds N,N-methylenebisacrylamide (MBA), and introduces nitrogen into the system, and finally adds an initiator to carry out a polymerization reaction to obtain a reaction mixture slurry.
[0051] In the present invention, the amount of the MOF powder is preferably 40% to 60% of the mass of the entire material; too low a MOF content will result in insufficient water absorption of the material under low relative humidity conditions, and too high a MOF content will make it difficult to shape the entire material.
[0052] In the present invention, the hydrophilic high molecular organic polymer is preferably selected from polyisopropylacrylamide (PNIPAM) and / or polyacrylic acid (PAA), more preferably polyisopropylacrylamide or polyacrylic acid. The present invention has no particular restriction on the source of the hydrophilic high molecular organic polymer, and commercially available products known to those skilled in the art can be used.
[0053] In the present invention, the binder is preferably selected from one or more of sodium alginate (SA), sodium carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), and polyvinyl pyrrolidone (PVP), and more preferably sodium alginate (SA) or sodium carboxymethyl cellulose (CMC). The present invention has no particular restrictions on the source of the binder, and commercially available products known to those skilled in the art can be used.
[0054] In the present invention, the mass ratio of the hydrophilic high molecular organic polymer to the binder is preferably 1: (0.5-2), more preferably 1: 1; too low a ratio will cause the excess binder to block the pore structure of the MOF itself, thereby resulting in a decrease in water absorption performance, while too high a ratio will cause the binder to be unable to maintain microsphere molding, that is, the polymer slurry cannot maintain a spherical shape after being dripped into the curing agent.
[0055] In the present invention, the initiator is preferably selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobisisobutylamidine hydrochloride, hydrogen peroxide, ammonium persulfate, potassium persulfate, benzoyl peroxide, tert-butyl benzoyl peroxide, and methyl ethyl ketone peroxide, and more preferably potassium persulfate K2(SO4)2. The present invention has no particular restrictions on the source of the initiator, and commercially available products known to those skilled in the art can be used.
[0056] In the present invention, the polymerization reaction process is always maintained in a nitrogen-filled and heated state.
[0057] In the present invention, the temperature of the polymerization reaction is preferably 0°C to 80°C, more preferably 50°C; wherein the low temperature condition of 0°C is controlled by an ice bath condition, and the temperature above 20°C is controlled by water bath heating. Too low a reaction temperature will lead to a decrease in the reaction rate, so a catalyst needs to be added to catalyze the polymerization reaction, and too high a reaction temperature will destroy the porous structure of the MOF itself, so the suitable reaction temperature is 0°C to 80°C.
[0058] In the present invention, the polymerization reaction time is preferably 0.5h to 1h, more preferably 30min; too low a reaction time will lead to incomplete polymerization reaction and failure of subsequent granulation process to form, while too long a reaction time will lead to reduced preparation efficiency, so the appropriate reaction time is 0.5h to 1h.
[0059] After obtaining the reaction mixture slurry, the present invention drips the obtained reaction mixture slurry into a curing agent for granulation, and obtains a MOF composite microsphere material after washing and freeze drying (freeze drying) (in a preferred embodiment of the present invention, the MOF is MOF-303; the MOF composite microsphere is PNIPAM / MOF microsphere or PAA / MOF microsphere).
[0060] In the present invention, the curing agent is preferably selected from one or more of calcium chloride solution, aluminum sulfate solution, and copper sulfate solution, and more preferably calcium chloride solution. The present invention has no particular restrictions on the source of the curing agent, and commercially available products known to those skilled in the art can be used. In a preferred embodiment of the present invention, the curing agent is saturated CaC l2 Solution.
[0061] In the present invention, the granulation process is preferably specifically as follows:
[0062] The reaction mixture slurry is dripped into the curing agent, and the beads are cross-linked in the curing agent for 20 to 40 minutes before being washed with water. In the present invention, a peristaltic pump is preferably used to drip the reaction mixture slurry into the curing agent.
[0063] The present invention adopts the crosslinking time of the above microspheres in the curing agent. Too short a crosslinking time will lead to poor mechanical stability of the material, and the spheres are easily broken after drying, while too long a crosslinking time will reduce the preparation efficiency. Therefore, the appropriate crosslinking time is 20 minutes to 40 minutes.
[0064] In the present invention, the freeze-drying process is preferably as follows:
[0065] The washed beads are frozen in liquid nitrogen for 5 to 15 minutes, and then the material is placed in a freeze dryer for freeze drying to obtain a MOF composite microsphere material. The drying method of the present invention is the above-mentioned freeze drying. The conventional heat drying method will destroy the pore structure of the overall material due to the diffusion of water vapor during the drying process, thereby affecting the water absorption performance of the final product.
[0066] The preparation method provided by the present invention has simple process, mild conditions, easy control, low energy consumption and thus energy saving, strong water collection performance, and is environmentally friendly, and has broad application prospects.
[0067] The present invention also provides a MOF composite microsphere material, which is prepared by the preparation method described in the above technical solution. The preparation method (or molding method) of the MOF composite microsphere material provided by the present invention mainly includes the following steps: using MOF-303 powder prepared by optimized amplification synthesis, introducing hydrophilic high molecular organic polymer and binder, etc., and preparing MOF composite microsphere material with macroscopic morphology and good mechanical properties by thermal polymerization and extrusion granulation; the material exhibits good water absorption performance in a wide range of humidity, and the maximum water adsorption capacity of the prepared poly (N-isopropylacrylamide) / MOF-303 microspheres reaches 2.14g / g, and the maximum water adsorption capacity of polyacrylic acid / MOF-303 microspheres reaches 3.84g / g, and has good recycling performance. Compared with the prior art, the preparation method provided by the present invention is to integrate MOF and polymer polymerization and granulation, more uniformly mix MOF and water-absorbing materials, and prepare a molded composite material with excellent water vapor adsorption performance and certain mechanical properties by microsphere granulation technology.
[0068] Compared with the prior art, the present invention has the following technical advantages:
[0069] (1) At present, the MOF powder materials prepared by the prior art have air gaps, poor mechanical strength, limited water absorption capacity, and the powder is easy to lose and difficult to recycle. The present invention introduces hydrophilic high molecular organic polymers and binders, etc., and uses a curing agent for granulation to obtain a MOF molded composite material with certain mechanical strength and water collection performance. It has good water absorption capacity under various humidity conditions, is easy to recycle, and can be recycled.
[0070] (2) The preparation method provided by the present invention has the advantages of simple process, low cost, extremely high water absorption capacity and low energy consumption.
[0071] The invention provides a method for preparing a MOF composite microsphere material, comprising the following steps: a) adding 3,5-pyrazoledicarboxylic acid into water to dissolve it, then adding hydroxyaluminum and an inorganic base to react, washing and drying to obtain MOF powder; b) mixing the MOF powder obtained in step a) with a hydrophilic macromolecular organic polymer, a binder and water, then adding N,N-methylenebisacrylamide, introducing nitrogen into the system, and finally adding an initiator to carry out polymerization reaction to obtain a reaction mixture slurry; c) dripping the reaction mixture slurry obtained in step b) into a curing agent to granulate, washing and freeze-drying to obtain the MOF composite microsphere material. Compared with the prior art, the preparation method provided by the present invention selects specific raw materials and specific process steps to achieve better overall interaction: directly using the dispersion system in the MOF preparation process, adding hydrophilic high molecular organic polymer and binder, and then dripping the slurry into the curing agent with a peristaltic pump for granulation to obtain uniform MOF composite microspheres; by adding molding materials and functional materials, the original MOF powder has a plastic shape, certain mechanical strength, excellent water absorption performance, desorption capacity and circulation performance. The experimental results show that the MOF composite microsphere material prepared by the preparation method provided by the present invention has the advantages of both MOF and polymer, and is controllable in size, good in mechanical strength, and excellent in water absorption performance in various humidity ranges, and can be applied to various practical application scenarios.
[0072] At the same time, the preparation method provided by the present invention has simple process, mild conditions, easy control, low energy consumption and thus energy saving, strong water collection performance, environmental friendliness, and broad application prospects.
[0073] In order to further illustrate the present invention, the following examples are used to explain the present invention in detail. The present invention prepares a MOF composite microsphere material ( Figure 1 ), forming a granular material that has the advantages of both MOF and polymer, with controllable size, certain mechanical strength, and conforming to actual application scenarios; at the same time, the present invention optimizes the preparation process, and investigates the influence of factors such as polymer type and component ratio on the material formability and water adsorption performance, and selects better reactant conditions based on water vapor adsorption performance as an evaluation index, and verifies the performance stability of the prepared MOF microspheres through a variety of characterization methods.
[0074] The raw materials used in the following examples of the present invention are all commercially available; the preparation methods, materials, structures or composition ratios and other features not explicitly described in the following examples of the present invention are all regarded as common technical features disclosed in the prior art.
[0075] Example 1
[0076] Preparation of PNIPAM / MOF microspheres:
[0077] The hydrophilic high molecular organic polymer raw material selected in this embodiment is N-isopropylacrylamide (NIPAM). Add 200mL of deionized water to a beaker, then add 15.61g of H2PZDC, place the beaker in a water bath, completely dissolve at 70°C until the solution is clear and transparent, then add 18.20g of HCA and 4g of NaOH, react at 90°C for 1h, wash twice with deionized water and methanol respectively, skim off the supernatant after the last wash and centrifuge, place in a 90°C oven and dry overnight to obtain MOF powder. Add MOF powder, NIPAM, SA and 40mL of deionized water (see Table 1 for the specific amount of materials added) to a 100mL three-necked flask in sequence, stir evenly with an electric stirrer (400rpm), and heat to 50°C with a water bath. Then add 0.15g MBA, and introduce nitrogen into the system. After 15 minutes of ventilation, add 0.1g K2(SO4)2 as an initiator to start the polymerization reaction. During the polymerization reaction, keep the nitrogen and heating state, and stop the reaction after 30 minutes of polymerization. Then use a peristaltic pump to drop the slurry after the reaction into a saturated CaCl2 solution for granulation. The obtained beads are cross-linked in the solution for 30 minutes and then washed with a large amount of deionized water. Then freeze the beads in liquid nitrogen for 10 minutes, and finally freeze dry them in a freeze dryer to obtain PNIPAM / MOF microspheres.
[0078] Table 1 PNIPAM / MOF microsphere synthesis reactant dosage
[0079]
[0080] The finished product was tested and found to have the highest specific surface area and water absorption performance, as well as the best thermal stability. Since the dosage of MOF was 50% (molar number) of the total dosage, the BET specific surface area of PNIPAM / MOF-4 was close to the theoretical value (500-600m 2 / g), and the micropore volume was well retained, which confirmed that PNIPAM / MOF-4 can combine the water adsorption capacity of MOF materials under low humidity conditions and polymer materials under high humidity conditions.
[0081] Example 2
[0082] Preparation of PAA / MOF microspheres:
[0083] The hydrophilic high molecular organic polymer raw materials selected in this embodiment are acrylic acid (AA) and acrylamide (AM), and the other preparation methods are the same as those in Example 1. The dosages of the specific materials are shown in Table 2.
[0084] Table 2. Dosage of reactants for PAA / MOF microsphere synthesis
[0085]
[0086] The BET specific surface area of PAA / MOF-1 is 152 m 2 / g, which is significantly lower than that of pure MOF-303. In addition, the micropore volume of PAA / MOF-1 is only 0.036cm 3 / g, compared with the original value of MOF-303 0.42cm 3 / g, a decrease of more than 90%. This significant change indicates that the microporous structure was significantly affected during the composite process. The introduction of PAM further enhanced the composite effect, and the BET specific surface area of PAA / MOF-2 was further reduced to 120 m 2 / g, micropore volume is 0.005cm 3 / g. These results indicate that although PAM may promote the order of the surface structure of the material, it also shows that its presence in the pores significantly limits the available volume of the pores. PAA / MOF-1 and PAA / MOF-2 have similar thermal stabilities and remain stable before 250°C.
[0087] Example 3
[0088] Water vapor adsorption capacity of PNIPAM / MOF microspheres:
[0089] The PNIPAM / MOF microspheres with different ratios in Example 1 were subjected to water vapor adsorption test. The microspheres obtained by granulation of MOF were light yellow under dry conditions. After absorbing water, the surface of the MOF microspheres was moist and the color deepened, with obvious bonding phenomenon ( Figure 2 ).like Figure 3 As shown in the figure, the MOF microspheres synthesized at a SA / NIPAM ratio of 1:1 (i.e., PNIPAM / MOF-4) showed the highest water adsorption capacity, which can reach 2.14 g / g at a relative pressure of P / P0=0.8, which is 4.6 times that of pure MOF materials. PNIPAM / MOF-4 also showed a water vapor adsorption working range under full humidity conditions. At a relative pressure of 0.1, the water absorption capacity was similar to that of pure MOF. When the relative pressure reached 0.2, the water adsorption capacity of MOF microspheres began to exceed that of pure MOF. At P / P0=0.2, the water adsorption capacity was 0.48 g / g, which was 1.3 times that of pure MOF. This shows that the hydrophilic polymer and MOF of PNIPAM / MOF-4 have a good synergistic effect under low humidity conditions, which improves the water absorption capacity of the overall material under low humidity conditions.
[0090] Example 4
[0091] Effect of PAA neutralization degree on water vapor adsorption capacity:
[0092] Two PAAs with different neutralization degrees (80% and 100%) were selected. From the perspective of their respective water absorption performance, except for PAA / MOF-2 which was lower at RH=10%, the water absorption performance of the overall material prepared by 100% neutralization PAA was better under other humidity conditions ( Figure 4 ).
[0093] Example 5
[0094] Effect of binder on water vapor adsorption capacity:
[0095] Two binders (SA and CMC) were selected for water adsorption testing. There was no significant difference in the surface morphology of MOF microspheres using CMC and SA as binders, but the water absorption performance of the former was much lower than that of the latter. Under 80% relative humidity conditions, the water vapor adsorption of the former was only 1 / 9 of that of the latter ( Figure 5 ). This indicates that the MOF microspheres using SA as a binder have higher hydrophilicity and more effective gel network structure.
[0096] Example 6
[0097] Effect of curing agent on water vapor adsorption capacity:
[0098] Three curing agents were selected, namely 5wt% CaCl2, CuCl2 and AlCl3 solutions. The obtained MOF microspheres showed different colors due to different cross-linked cations. The MOF microspheres using CaCl2 and AlCl3 as curing agents were white, while the MOF microspheres using CuCl2 as curing agent were blue. In terms of water absorption performance, the choice of curing agent is CaCl2>AlCl3>CuCl2. Under various humidity conditions, the water absorption performance of MOFs using CaCl2 as curing agent is twice that of the other two ( Figure 6 ).
[0099] Example 7
[0100] Water vapor adsorption capacity of PAA / MOF microspheres:
[0101] Examples 4 to 6 preliminarily prove that among the reactant conditions, the best reaction conditions for synthesizing MOF microspheres are to select 100% neutralized PAA and SA as binders and CaCl2 as curing agent (i.e. PAA / MOF-1 and PAA / MOF-2). Before absorbing water, the MOF microspheres are white and light in texture. After absorbing water, a large amount of water is adsorbed on the surface and the water molecules form agglomerates ( Figure 7 ).like Figure 8As shown in the figure, PAA / MOF-1 shows a higher water vapor adsorption capacity than pure MOF-303 in the whole humidity range. This may be because the introduction of PAA increases the hydrophilicity of the material, thereby increasing its adsorption affinity for water molecules. The water vapor adsorption capacity of PAA / MOF-2 under extremely low humidity conditions (10%) is lower than that of pure MOF materials. This is caused by the introduction of PAM. Under relatively high humidity conditions, the water absorption capacity of PAA / MOF-2 is slightly inferior to that of PAA / MOF-1, but it is still much higher than that of pure MOF materials.
[0102] Example 8
[0103] Water vapor adsorption, desorption and recycling capabilities of PAA / MOF microspheres:
[0104] After the PAA microspheres absorbed water, their thermogravimetric curves at different heating rates were tested to calculate the desorption activation energy. The desorption activation energy of PAA-MOF-1 (35.52KJ / mol) was lower than that of PAA-MOF-2 (38.29KJ / mol). This is because the addition of AM makes the MOF microspheres more swellable, making it easier to release the adsorbed water. Through the cyclic performance test of the microspheres, it was found that after 5 cycles, the water absorption of PAA-MOF-1 and PAA-MOF-2 could reach 70% and 88% of the initial value, respectively. The cyclic stability of PAA / MOF-2 with the addition of PAM is better than that of PAA / MOF-1.
[0105] Comparative Example 1
[0106] The water absorption of the composite microsphere material with a polymer to binder ratio of 1:1 is 0.21 g / g at RH = 10%, 0.48 g / g at RH = 20%, and 2.14 g / g at RH = 80%. The water absorption of the composite microsphere material with a polymer to binder ratio of 3:2 is 0.20 g / g at RH = 10%, 0.40 g / g at RH = 20%, and 1.42 g / g at RH = 80%.
[0107] The experimental results show that compared with different raw material ratios, the water absorption performance of the polymer to binder ratio of 1:1 is better.
[0108] Comparative Example 2
[0109] The water absorption of the composite microsphere material using polyacrylic acid as the polymer is 0.40 g / g at RH = 10%, 0.55 g / g at RH = 20%, and 2.23 g / g at RH = 80%. The water absorption of the composite microsphere material using polyisopropylacrylamide as the polymer is 0.21 g / g at RH = 10%, 0.48 g / g at RH = 20%, and 2.14 g / g at RH = 80%.
[0110] The experimental results show that compared with different types of polymers, polyacrylic acid has better water absorption performance.
[0111] Comparative Example 3
[0112] The water absorption of the composite microsphere material using sodium alginate as a binder is 0.40 g / g at RH = 10%, 0.55 g / g at RH = 20%, and 2.23 g / g at RH = 80%. The water absorption of the composite microsphere material using sodium carboxymethyl cellulose as a binder is 0.08 g / g at RH = 10%, 0.13 g / g at RH = 20%, and 0.33 g / g at RH = 80%.
[0113] The experimental results show that compared with different types of adhesives, sodium alginate has better water absorption performance.
[0114] Comparative Example 4
[0115] The water absorption of the composite microsphere material using calcium chloride solution as a curing agent is 0.40 g / g at RH = 10%, 0.55 g / g at RH = 20%, and 2.23 g / g at RH = 80%. The water absorption of the composite microsphere material using aluminum sulfate solution as a curing agent is 0.07 g / g at RH = 10%, 0.29 g / g at RH = 20%, and 0.65 g / g at RH = 80%.
[0116] The experimental results show that compared with different types of curing agents, the water absorption performance of calcium chloride solution is better.
[0117] In summary, compared with Comparative Document 1, the synthesis process of MOF-303 uses less sodium hydroxide and a shorter reaction time, which greatly improves the production efficiency of the product, and the washing and activation steps are simpler and consume less energy; compared with Comparative Document 2, the water absorption performance of the composite microsphere material is better, and the water absorption in the entire humidity range is higher than that of the composite material in the comparative document.
[0118] Therefore, the embodiment of the present invention is obtained through a large number of experimental screenings. The screening is carried out by comparing the water absorption of the composite microsphere material. The best proportion of MOF is 50%, and the remaining main additions are polymers and binders, and the best ratio of polymers and binders is 1:1, and the best mass concentration of the curing agent is 5%wt; in the selection of MOF, MOF-303 is better than other MOFs; in the selection of polymers, polyacrylic acid is better than polyisopropylacrylamide; secondly, in the selection of binders, sodium alginate is better than sodium carboxymethyl cellulose and polyvinyl pyrrolidone; in the selection of initiators, potassium persulfate is better than ammonium persulfate; in the selection of curing agents, calcium chloride solution is better than aluminum sulfate solution and copper sulfate solution. It can be seen that the best raw material combination of the present invention is MOF-303, polyisopropylacrylamide, sodium alginate, potassium persulfate, and calcium chloride solution.
[0119] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a MOF composite microsphere material, comprising the following steps: a) adding 3,5-pyrazoledicarboxylic acid into water to dissolve it, then adding hydroxyaluminum and an inorganic base to react, washing and drying to obtain MOF powder; b) mixing the MOF powder obtained in step a) with a hydrophilic high molecular organic polymer, a binder and water, adding N,N-methylenebisacrylamide, introducing nitrogen into the system, and finally adding an initiator to carry out a polymerization reaction to obtain a reaction mixture slurry; c) dripping the reaction mixture slurry obtained in step b) into a curing agent for granulation, washing and freeze-drying to obtain a MOF composite microsphere material.
2. The preparation method according to claim 1, characterized in that: The dissolving process in step a) is specifically as follows: adding water to a beaker, then adding 3,5-pyrazoledicarboxylic acid, placing the beaker in a water bath, and completely dissolving at 60° C. to 80° C. until the solution is clear and transparent; The inorganic base is selected from NaOH and / or KOH; The reaction temperature is 85°C to 95°C and the reaction time is 0.5h to 1.5h; The washing method is specifically to use water and methanol to wash 1 to 3 times respectively; The drying temperature is 85° C. to 95° C., and the drying time is 10 h to 30 h.
3. The preparation method according to claim 1, characterized in that: The hydrophilic high molecular organic polymer in step b) is selected from polyisopropylacrylamide and / or polyacrylic acid.
4. The preparation method according to claim 1, characterized in that: In step b), the binder is selected from one or more of sodium alginate, sodium carboxymethyl cellulose, polyvinyl alcohol and polyvinyl pyrrolidone.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the hydrophilic high molecular organic polymer to the binder in step b) is 1:(0.5-2).
6. The preparation method according to claim 1, characterized in that: The initiator in step b) is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobisisobutylamidine hydrochloride, hydrogen peroxide, ammonium persulfate, potassium persulfate, benzoyl peroxide, tert-butyl benzoyl peroxide, and methyl ethyl ketone peroxide.
7. The preparation method according to claim 1, characterized in that: The polymerization reaction temperature in step b) is 0°C to 80°C, and the reaction time is 0.5h to 1h.
8. The preparation method according to claim 1, characterized in that: In step c), the curing agent is selected from one or more of calcium chloride solution, aluminum sulfate solution and copper sulfate solution.
9. The preparation method according to claim 1, characterized in that: The granulation process in step c) is specifically as follows: The reaction mixture slurry is dripped into the curing agent, and the beads are cross-linked in the curing agent for 20 to 40 minutes and then washed with water; The freeze-drying process is specifically as follows: The washed beads were frozen in liquid nitrogen for 5 to 15 minutes, and then the material was placed in a freeze dryer for freeze drying to obtain a MOF composite microsphere material.
10. A MOF composite microsphere material, characterized in that: The preparation method is described in any one of claims 1 to 9.
Citation Information
Patent Citations
Forming method of ultra-microporous MOF adsorbent material
CN112705168A
Extruded metal-organic framework materials and methods for production thereof
CN113272053A
Method for preparing injection molding product by using metal organic framework material
CN117841320A